Features of tissue oxygen metabolism in the traumatic brain injury and diabetes - V.M. Meretskyi (Zaporozhye State Medical University, 2013)
The paper presents the analysis of tissue oxygen metabolism in traumatic brain injury and diabetes. It was shown an imbalance between systemic oxygen supply and the need for it due to decreased oxygenation of arterial and mixed venous blood, the total content of oxygen in arterial blood, increased levels of methemoglobin, the trend of the degree of pulmonary and hemic hypoxia increase, compensatory volume increase of cardiac output insuffi cient for satisfactory oxygen delivery in a traumatic brain injury. Under conditions of the TBI complicated by diabetes, there was more pronounced disturbance in oxygenation of arterial and mixed venous blood with the slowdown of their recovery due to the participation of pulmonary and hemic hypoxic components. Hemodynamic disturbances in the absence of growth in cardiac output and oxygen delivery speed changes, leading to destabilization of the oxygen balance, were observed.